Successful Treatment of Chidamide and Cyclosporine for Refractory/Relapsed Angioimmunoblastic T Cell Lymphoma With Evans Syndrome: A Case Report With Long-Term Follow-Up - Zhu, Fang; Li, Qiuhui; Pan, Huaxiong; Xiao, Yin; Liu, Tao; Liu, Xinxiu; Li, Juan; Wu, Gang; Zhang, Liling (Frontiers in Oncology, 2020)
Background: Refractory/relapsed angioimmunoblastic T cell lymphoma (AITL) with Evans syndrome is a very rare condition with a poor prognosis. There is no evidence-based treatment strategy for refractory/relapsed AITL with Evans syndrome. Case presentation: A 51-year-old female was admitted to our hospital with multiple enlarged bilateral cervical lymph nodes, more than one week-long chest distress, and night sweats in July 2014. An excision biopsy of the left cervical enlarged lymph node revealed AITL. However, the patient showed resistance to the first-line chemotherapy for AITL and was diagnosed with refractory AITL. Complete remission was achieved after the salvage treatment with the combination of chemotherapy, radiotherapy, and immunomodulatory agent lenalidomide. Unfortunately, 12 months later, the patient suffered from disease progression and was diagnosed as refractory/relapsed AITL with Evans syndrome according to the laboratory findings and imaging. With the diagnosis of refractory/relapsed AITL with Evans syndrome, the patient received the first-line treatment for Evans syndrome including prednisone and intravenous immunoglobulin. The response to the first-line treatment for Evans syndrome was poor. The combination regimen of chidamide (30mg, po, biw) and cyclosporine were administrated considering the treatment targeting simultaneously both refractory/relapsed AITL and Evans syndrome. The efficacy evaluation was complete remission. The last follow-up of the patient was Apr 30th, 2020, and no evidence of disease progression was observed. The overall survival of the patient was more than 70 months. Conclusions: The treatment for refractory/relapsed AITL combined with Evans syndrome remains challenging to patients and physicians. The combination of chidamide and cyclosporine may be an effective and tolerable regimen for the intractable AITL with Evans syndrome case and more observations are necessary to identify the efficacy and safety in the future.